2013
DOI: 10.1038/ejhg.2013.256
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of a pentaplex panel for MSI analysis without control DNA in a Brazilian population: correlation with ancestry markers

Abstract: Microsatellite instability (MSI) testing has been advocated for all newly diagnosed colorectal cancer patients. One of the most common tests is composed by a pentaplex panel of mononucleotides markers , which allows the analysis of MSI in tumors without the need of reference DNA. For that, it is fundamental to establish a quasi-monomorphic variation range (QMVR) for each marker. Herein, we aimed to establish the QMVR in a Brazilian healthy population, to evaluate the feasibility of MSI determination of tumors,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(65 citation statements)
references
References 42 publications
2
59
0
4
Order By: Relevance
“…The MSI evaluation was performed using a multiplex PCR comprising five quasimonomorphic mononucleotide repeat markers (NR27, NR21, NR24, BAT 25 and BAT26), as described by our group (20). The MSI status of the lesion was analyzed using GeneMapper 4.1 software (Applied Biosystems).…”
Section: Analysis Of Msimentioning
confidence: 99%
“…The MSI evaluation was performed using a multiplex PCR comprising five quasimonomorphic mononucleotide repeat markers (NR27, NR21, NR24, BAT 25 and BAT26), as described by our group (20). The MSI status of the lesion was analyzed using GeneMapper 4.1 software (Applied Biosystems).…”
Section: Analysis Of Msimentioning
confidence: 99%
“…126 had a microsatellite stable (MSS) genotype, 7 had MSI-L and none had MSI-H. In a previous study (Campanella et al, 2014), our group reported that in order to accurately determine MSI-L, the MSI markers of tumor tissue should be compared with the germ-line tissue of the patient. Therefore, for the seven cases with MSI-L, we isolated adjacent normal tissue and identified the presence of an identical MSI marker profile, thereby indicating a MSS phenotype.…”
Section: Resultsmentioning
confidence: 99%
“…Herein, we used a validated methodology that comprised five quasimonomorphic mononucleotide repeat markers to identify MSI (NR-27, NR-21, NR-24, (Boland et al, 1998), when an international consensus updated the recommendation and recommended that dinucleotide repeats be substituted for mononucleotide repeats because of improved sensitivity (Buhard et al, 2004). We utilized this new recommended methodology for this study -a methodology that has been recently validated by our group in the Brazilian population (Campanella et al, 2014). Other potential causes of differing results may be associated with tumor aggressiveness.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations